EFEKTIVITAS MODEL TREFFINGER BERBASIS LINGKUNGAN TERHADAP MOTIVASI BELAJAR KELAS X PELAJARAN EKONOMI SMA 2 SEKAYAM - Mesin, Emelia; Ulfah, Maria; Budiman, Jumardi (Universitas Tanjungpura, 2025)
The study aims to see the effectiveness of the environment-based Treffinger model on the motivation of learning economics class X at SMA 2 Sekayam. The Treffinger model is a learning strategy that encourages creativity through systematic problem-solving stages, while the environment-based approach provides a more contextual and relevant learning experience to real life. The research method used is a quasi-experiment in the form of Nonequivalent Control Group Design. The sample used two classes, namely the experimental class that was given the environment-based Treffinger model treatment and the control class that was not given treatment or used a conventional model. Data collection was carried out through a questionnaire that had been tested for validity and reliability. The normality test used Shapiro Wilk data which showed normally distributed data with a significance value of 0.613 for the experimental class and 0.568 for the control class. The results of the independent sample t-test showed a significant difference between the motivation of the experimental class and the control class with sig = (0.000